Evaluation of A 12-Month Pilot of Long-Term and Temporary Assisted Peritoneal Dialysis. Issue 3 (May 2017) - Bevilacqua, Micheli U.; Turnbull, Linda; Saunders, Sushila; Er, Lee; Chiu, Helen; Hill, Penny; Singh, Rajinder S.; Levin, Adeera; Copland, Michael A.; Jamal, Abeed; Brumby, Catherine; Dunne, Orla; et al.
Background: Peritoneal dialysis (PD) is challenging for patients with functional limitations, and assisted PD can support these patients, but previous reports of assisted PD have not examined the role of temporary assisted PD and had difficulty identifying adequate comparator cohorts. Methods: Peritoneal Dialysis Assist (PDA), a 12-month pilot of long-term and temporary assisted PD was completed in multiple PD centers in British Columbia, Canada. Continuous cycler PD (CCPD) patients were identified for PDA by standardized criteria, and service could be long-term or temporary/respite. The PDA program provided daily assistance with cycler dismantle and setup, but patients remained responsible for cycler connections and treatment decisions. Outcomes were compared against both the general CCPD population and patients who met PDA criteria but were not enrolled (PDA-eligible). Results: Fifty-three PDA patients had an 88% 1-year death- and transplant-censored technique survival that was similar to the general CCPD cohort (84%) and PDA-eligible cohort (86%). The PDA cohort had lower peritonitis rates (0.18 episodes/patient-year vs 0.22 and 0.36, respectively), but higher hospitalization (55% vs 34% and 35%, respectively). Long-term PDA cost approximately CDN15, 000/year in addition to existing dialysis costs. A total of 8/11 respite PDA patients (73%) returned to self-care PD after a median PDA use of 29 days, which costs 1, 250/patient. Conclusions: Peritoneal Dialysis Assist provides effective support to functionally-limited CCPD patients and yields acceptable clinical outcomes. The program costs less than transfer to HD or long-term care, which represents cost minimization for failing self-care PD patients. Respite PDA provides effective temporary support; most patients returned to self-care PD and service was cost-effective compared with alternatives of hospitalization or transfer to HD.